The Troubled Frame Narrative: Bad Listening in Late Imperial Russia. Issue 4 (1st September 2013) - SAFRAN, GABRIELLA
Abstract : Technological change, the appearance of a new entertainment market, the great reforms, and the rise of new professions all required the subjects of the Russian Empire to listen differently in the final decades of the nineteenth century. As demonstrated in recent explorations by historians of the anglophone and francophone worlds, people react to what is perceived as an intolerable increase of noise in modernity by refusing to listen. This article contends that the new listening practices of the 1870s gave rise to a new literary genre, the "troubled frame narrative, " in which listening is thematized and portrayed as difficult and unpleasant; listeners yearn to escape. Close readings of Dostoevskii's "The Meek One, " Chekhov's "Drama, " and Tolstoy's "Kreutzer Sonata" describe the interactions between new genres of listening and a new literary phenomenon.